JAMBI : DAERAH RANTAU ETNIS MINANGKABAU - Arif Rahim (Jurnal Ilmiah Dikdaya, 2017)
Abtract : This paper discusses the area of Jambi as Minangkabau ethnic seacoast area. Through the history of the structural approach can be concluded that the existence of Jambi as Minangkabau ethnic rantau been going on since long. In general phenomenon driven by the Minang ethnic wander. Natural factors, economic, political, social and cultural education. Especially for the area of Jambi process to migrate is because the two regions is a geographical entity united by Batang Hari river. In addition to economic factors and trading mainly mining and gold trade has triggered a wave of ethnic Minang migration in large numbers, especially to the area of Jambi Hulu. The development of education in West Sumatra since the mid-19th century, which goes hand in hand with the development of the bureaucratic system of colonial rule, a new driving factor in order to seize opportunities as employees, bureaucrats, teachers, and other professional workers The existence of ethnic Minang Jambi region coupled with the interaction between them and the local community . That caused a lot Jambi region receive the influence of Minangkabau.The effect is especially apparent in the field of social and cultural life .